Identification of Motives of Children Working as Street Clowns in Manado City, North Sulawesi Province - Palar, Novie R. A.; Kandowangko, Nicolaas; Ruru, Joorie M.; Goni, Shirley Y. V. I. (Journal of Management and Administration Provision, 2024)
Various activities are carried out by the community to meet their living needs. One activity that has become a new phenomenon seen in Manado City is street clowns. The phenomenon of street clowns can be found at intersections and at the entrances and exits of the Boulevard shopping area. They try to entertain the general public and drivers so that they get money, although the amount is not much. However, most of these street clowns are of school age and should not be active to earn income. This phenomenon is actually different from the culture of the Manado City Community in carrying out activities to earn income. This study was conducted to identify and analyze the motives of children who work as street clowns in Manado City. The results of this study can be used as a recommendation for the Manado City government in compiling a program to strengthen social institutions in the Community and in maintaining public order in public places. This study will be conducted using a qualitative method with a phenomenological approach. Data were collected through interviews with children who work as street clowns and with the leaders of the Social and Community Empowerment Service and the leaders of the Manado City Civil Service Police Unit. Conducting observations on the activities of street clown professions and collecting other supporting data through internet-based electronic library searches such as Google Scholar and ResearchGate. Data analysis through the stages of data reduction, data presentation and drawing conclusions and data verification. Children who work as street clowns in Manado City are school-age children. The main motive is to help parents meet their living needs through additional income. They come from suburban areas and have a community. The hope of feeling affection and attention and having time to play is very much needed by them.